Effects of Oral and Transdermal Estrogen Replacement Therapy on Markers of Coagulation, Fibrinolysis, Inflammation and Serum Lipids and Lipoproteins in Postmenopausal Women - Vehkavaara, Satu; Silveira, Angela; Hakala-Ala-Pietilä, Tiina; Virkamäki, Antti; Hovatta, Outi; Hamsten, Anders; Taskinen, Marja-Riitta; Yki-Järvinen, Hannele (Thrombosis and Haemostasis, 2001)
We compared the effects of oral estradiol (2 mg), transdermal estradiol (50 g), and placebo on measures of coagulation, fibrinolysis, inflammation and serum lipids and lipoproteins in 27 postmenopausal women at baseline and after 2 and 12 weeks of treatment. Oral and transdermal estradiol induced similar increases in serum free estradiol concentrations. Oral therapy increased the plasma concentrations of factor VII antigen (FVIIag) and activated factor VII (FVIIa), and the plasma concentration of the prothrombin activation marker prothrombin fragment 1+2 (F1+2). Oral but not transdermal estradiol therapy significantly lowered plasma plasminogen activator inhibitor-1 (PAI-1) antigen and tissue-type plasminogen activator (tPA) antigen concentrations and PAI-1 activity, and increased D-dimer concentrations, suggesting increased fibrinolysis. The concentration of soluble Eselectin decreased and serum C-reactive protein (CRP) increased significantly in the oral but not in the transdermal or placebo groups. In the oral but not in the transdermal or placebo estradiol groups low-density-lipoprotein (LDL) cholesterol, apolipoprotein B and lipoprotein (a) concentrations decreased while high-density-lipoprotein (HDL) cholesterol, apolipoprotein AI and apolipoprotein AII concentrations increased significantly. LDL particle size remained unchanged. In summary, oral estradiol increased markers of fibrinolytic activity, decreased serum soluble E-selectin levels and induced potentially antiatherogenic changes in lipids and lipoproteins. In contrast to these beneficial effects, oral estradiol changed markers of coagulation towards hypercoagulability, and increased serum CRP concentrations. Transdermal estradiol or placebo had no effects on any of these parameters. These data demonstrate that oral estradiol does not have uniformly beneficial effects on cardiovascular risk markers and that the oral route of estradiol administration rather than the circulating free estradiol concentration is critical for any changes to be observed.
Keywords: Atherosclerosis; hemostasis; estradiol; cholesterol; triglycerides